Penerapan Media Quizizz Materi Fluida Statis Untuk Meningkatkan Hasil Belajar Fisika Kelas XI (IPF: Inovasi Pendidikan Fisika, 2022)
The development of technology is very useful in the education world. One of the impacts of technological developments on the education world is the development of learning media. Learning media is made as attractive as possible to increase the student’s interest which affects their learning outcomes. This study aims to analyze the use of Quizizz media as an evaluation tool to increase student learning outcomes in class XI physics using static fluid using Quizizz media. The method in this study is an experiment with a Quasi-Experimental Design. The sample used in this study amounted to 80 students from a total population of 308 students who came from two classes XI science.. The sample is divided into two classes, namely experimental and control. The experimental class was treated using Quizizz media (paperless-based test), while the control class was given a paper-based test. The instrument in this research is multiple-choice questions. Before being tested on students, the validity of the instrument was tested and the results were valid. According to the results of research that has been carried out, the difference in the average pretest-post-test between the experimental class and the Quizizz treatment is higher than the control class with a value of 39.37 so it is categorized as moderate. The significance value in the post-test t-test of the two classes got a value of 0.019 which means there is a difference. To find out the improvement in physics learning outcomes for class XI static fluid material using Quizizz media, the n-gain test was carried out. Obtained a significance value of 0.008 which means it is smaller than 0.05 and the t-count is greater than t- table, therefore it can be said that the results of the hypothesis test Ha are accepted. So it can be said that the application of Quizizz media in static fluid material can affect the improvement of student learning outcomes in class XI. So Quizizz can be applied as an evaluation tool to measure students' abilities.